Synthesis of novel thiazole, imidazole, benzimidazole, and benzothiazole derivatives incorporating 2‐phenoxy‐N‐arylacetamide unit as novel hybrid molecules. (27th January 2023) - Diab, Hadeer M.; Mohamed, Dina Mamdouh; Darweesh, Ahmed F.; Abdelhamid, Ismail A.; Elwahy, Ahmed H. M.
Abstract: Novel 2‐phenoxy‐ N ‐phenylacetamide hybrids with heterocyclic scaffolds such as thiazoles, imidazoles, benzimidazoles, and benzothiazoles were synthesized efficiently in this study. The reaction of the appropriate α‐haloketone with the corresponding thioamide derivatives in EtOH/DMF at reflux in the presence of a few drops of TEA produced good yields of 2‐aryl‐ or heteroarylthiazoles. A one‐pot three‐component reaction of 1, 2‐diketone with aldehydes and ammonium acetate in methanol at reflux yielded imidazole derivatives. It was also feasible to synthesize benzimidazoles, benzothiazoles, or imidazo[4, 5‐ b ]pyridines by employing the reactions of the appropriate aldehydes with o ‐phenylenediamine, 2‐aminothiophenol, or 2, 3‐diaminopyridine, respectively, in ethanol at reflux in the presence of NaHSO3 . The new compounds' structures were validated using spectrum data and elemental analyses. Abstract : Synthesis of 2‐phenoxy‐N‐phenylacetamide hybrids with thiazoles, imidazoles, benzimidazoles, and benzothiazoles.